2015
DOI: 10.1517/14712598.2015.1036026
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab emtansine in advanced human epidermal growth factor receptor 2-positive breast cancer

Abstract: T-DM1 (Kadcyla) has become the treatment of choice in second-line and beyond for patients with advanced HER2-expressing breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…ADCs, consisting of monoclonal antibodies conjugated to potent chemotherapeutics via a stable linker, have given rise to a highly efficacious class of anticancer drugs [ 2 ]. Currently, there are two ADCs approved, one for the treatment of relapsed/refractory Hodgkin’s lymphoma and systemic anaplastic large cell lymphoma (brentuximab vedotin) [ 3 ], and the other for advanced/metastatic human epidermal growth factor receptor 2–positive breast cancer (trastuzumab emtansine) [ 4 ]. In addition, there is a rapidly growing clinical pipeline with over 60 ADCs in development to target a wide range of blood cancers and solid tumors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…ADCs, consisting of monoclonal antibodies conjugated to potent chemotherapeutics via a stable linker, have given rise to a highly efficacious class of anticancer drugs [ 2 ]. Currently, there are two ADCs approved, one for the treatment of relapsed/refractory Hodgkin’s lymphoma and systemic anaplastic large cell lymphoma (brentuximab vedotin) [ 3 ], and the other for advanced/metastatic human epidermal growth factor receptor 2–positive breast cancer (trastuzumab emtansine) [ 4 ]. In addition, there is a rapidly growing clinical pipeline with over 60 ADCs in development to target a wide range of blood cancers and solid tumors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This likely contributes to the overall safety profile of T-DM1. 33 , 38 , 39 Finally, Yu et al 27 have concluded that the regimen of T-DM1 as well as pertuzumab in combination with trastuzumab and docetaxel is efficacious with fewer side effects as compared with other regimens through a network meta-analysis of six HER2-targeted treatment drugs and one naive standard treatment. Although that article only included a clinical study of T-DM1, it has been shown that T-DM1 is a better regimen.…”
Section: Discussionmentioning
confidence: 99%
“…These three compounds are well‐known tubulin inhibitors and both vincristine and vinblastine are routinely used to treat cancer patients whose cancer belongs to various histopathological types. Ado‐trastuzumab emtansine (T‐DM1) is a human epidermal growth factor receptor 2 (HER2) targeted antibody–drug conjugate composed of trastuzumab, a stable linker (4‐( N ‐maleimidomethyl)cyclohexane‐1‐carboxylate, MCC), and the cytotoxic agent DM1, which is mertansine, a derivative of maytansine . T‐DM1 underwent several successful Phase III clinical trials and it is now proposed as a treatment of choice in second line and beyond for patients with advanced HER2‐expressing breast cancer …”
Section: Mollusk‐derived Anticancer Agentsmentioning
confidence: 99%